2011
DOI: 10.1186/1471-2334-11-58
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation and transport of microbial-size particles in a pressure protected model burn unit: CFD simulations and experimental evidence

Abstract: BackgroundControlling airborne contamination is of major importance in burn units because of the high susceptibility of burned patients to infections and the unique environmental conditions that can accentuate the infection risk. In particular the required elevated temperatures in the patient room can create thermal convection flows which can transport airborne contaminates throughout the unit. In order to estimate this risk and optimize the design of an intensive care room intended to host severely burned pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…Further experiments are required to investigate the effects of various ventilation modes, though the scaling issues for thermal buoyancy and pressure effects may make this difficult in a small-scale, water-tank model like the one used here. Computational fluid dynamical (CFD) modeling of the airflows across doorways has been performed recently [24], but this is difficult to compare directly to these experimental results as they also take into account pressure and thermal differences across the doorway, which are both equal on either side of the doorway in the baseline experiments presented here. However, one interesting finding from the CFD modeling, the phenomenon of the back-flow of potentially contaminated air when a hinged-door is opened, has been observed in our qualitative experimental findings here, and demonstrated in the case report by Tang et al [23].…”
Section: Discussionmentioning
confidence: 99%
“…Further experiments are required to investigate the effects of various ventilation modes, though the scaling issues for thermal buoyancy and pressure effects may make this difficult in a small-scale, water-tank model like the one used here. Computational fluid dynamical (CFD) modeling of the airflows across doorways has been performed recently [24], but this is difficult to compare directly to these experimental results as they also take into account pressure and thermal differences across the doorway, which are both equal on either side of the doorway in the baseline experiments presented here. However, one interesting finding from the CFD modeling, the phenomenon of the back-flow of potentially contaminated air when a hinged-door is opened, has been observed in our qualitative experimental findings here, and demonstrated in the case report by Tang et al [23].…”
Section: Discussionmentioning
confidence: 99%
“…This study has shown that a substantial quantity of the deposited particles may have been in the micron or submicron size range, which has also been reported in modern literature [22,64]. As a result, certain infection inducing microorganisms that were thought to be predominantly airborne such as influenza or varicella, could deposit onto surfaces many meters way from the infectious source.…”
Section: General Observationsmentioning
confidence: 58%
“…The 2°C temperature difference between the anteroom and isolation room significantly affected the air transfer, especially in the rooms which had sliding doors. When the difference between the two rooms' temperatures is more than 2°C, the risk of transporting contaminated sources to the next room is higher due to thermal convective flows ( 24 , 28 ).…”
Section: Resultsmentioning
confidence: 99%